Diversion, Rights and Social Justice. (April 2021) - Smith, Roger
This article draws on historical understandings and contemporary models of diversion in order to develop a critical framework and agenda for progressive practice. The argument essentially revolves around the contention that typically diversionary interventions have been constrained by the contextual and ideological frames within which they operate. They have in some cases been highly successful in reducing the numbers of young people being drawn into the formal criminal justice system; however, this has largely been achieved pragmatically, by way of an accommodation with the prevailing logic of penal practices. Young people have been diverted at least partly because they have been ascribed a lesser level of responsibility for their actions, whether by virtue of age or other factors to which their delinquent behaviour is attributed. This ultimately sets limits to diversion, on the one hand, and also offers additional legitimacy to the further criminalisation of those who are not successfully 'diverted', on the other. By contrast, the article concludes that a 'social justice' model of diversion must ground its arguments in principles of children's rights and the values of inclusion and anti-oppressive practice.